Choosing Partners: Selection Priorities of Joint Liability Group Leaders - Sabin, N (PHYSICA-VERLAG GMBH & CO, 2023)
Joint liability credit groups are often formed through a self-selection process. Partner choice presents complex tradeoffs between behavioral expectations, risk diversification, monitoring, and enforcement. Most prior studies have found partner selection to be non-optimal financially. In this study, we explore social, spatial, economic, and demographic factors that may be driving the selection process. A unique analytical approach is used based on the selection order of partners in joint liability groups. We decompose a group leader s sequence of partner invitations into a series of ranked choices. The results indicate that socially and spatially proximate members are likely to be prioritized in the selection process, even though other potential members may possess stronger financial traits, such as higher monthly sales or business equity. There is also evidence of early selection based on gender, marital status, children, and matching business type. The analysis suggests that partner selection may be driven by social incentives and the avoidance of strategic default. More broadly, this study suggests which factors are prioritized when actors have choice over whom to partner with in a social dilemma.